Fatigue mechanism of yttrium-doped hafnium oxide ferroelectric thin films fabricated by pulsed laser deposition. Issue 5 (7th December 2016) - Huang, Fei; Chen, Xing; Liang, Xiao; Qin, Jun; Zhang, Yan; Huang, Taixing; Wang, Zhuo; Peng, Bo; Zhou, Peiheng; Lu, Haipeng; Zhang, Li; Deng, Longjiang; et al.
Abstract : We report a systematic study of the fatigue mechanism of yttrium-doped hafnium oxide (HYO) ferroelectric thin films deposited by pulsed laser deposition. Abstract : Owing to their prominent stability and CMOS compatibility, HfO2 -based ferroelectric films have attracted great attention as promising candidates for ferroelectric random-access memory applications. A major reliability issue for HfO2 based ferroelectric devices is fatigue. So far, there have been a few studies on the fatigue mechanism of this material. Here, we report a systematic study of the fatigue mechanism of yttrium-doped hafnium oxide (HYO) ferroelectric thin films deposited by pulsed laser deposition. The influence of pulse width, pulse amplitude and temperature on the fatigue behavior of HYO during field cycling is studied. The temperature dependent conduction mechanism is characterized after different fatigue cycles. Domain wall pinning caused by carrier injection at shallow defect centers is found to be the major fatigue mechanism of this material. The fatigued device can fully recover to the fatigue-free state after being heated at 90 °C for 30 min, confirming the shallow trap characteristic of the domain wall pinning defects.